Towards a national pre‐school vision screening programme. (28th April 2022) - Crippa, Jessica; Flaherty, Maree; Silveira, Sue
Abstract : The aim of the study is to examine common approaches to pre‐school vision screening, including the current New South Wales model which is known as Statewide Eyesight Preschooler Screening (StEPS) to determine whether the criteria set by the World Health Organization are fulfilled by StEPS, and therefore, whether there is sufficient justification to deploy a similar model nationally. A literature review was conducted to answer four key questions related to vision screening. The authors sought to review (i) the justification for vision screening of a pre‐school population; (ii) the principles and best approaches to vision screening such as how, where and who should conduct vision screening; (iii) the conditions that are targeted in vision screening; and (iv) the acceptable pass/fail vision screening criteria. The StEPS vision screening model is an accurate, reliable and economical way of screening for reduced vision at a time when neural plasticity allows improvement in vision following intervention. It fulfils World Health Organization criteria for a successful screening programme. StEPS has very high participation rates compared to other screening methods in Australia due to its unique model whereby screeners utilise early childhood settings to recruit and screen 4‐year‐old children. Due consideration should be given to deploying the StEPS vision screening model nationally.